Altas habilidades ou superdotação em contexto de educação matemática: ecos e expressividades - SOARES, Maria Eliana (Universidade Federal do Pará, 2023)
The study aimed analising expressivities of graduating students of the High School, with the indicative of High Abilities or Superdotation in context of Mathematical Education, and specifically, took: 1) identify manifestations of High Abilities or Superdotation in Students of the High School in intra school enviromment; 2) describe the expressiveness of the High Habilities or Superdotation in context of Mathematical Education; and, 3) to recognise in founds, elements which contribute for a comprehension and teacher’s action about the High Abilities ou Superdotation. It anchored itself in the epistemological bases of the Psychology (social, cognitive and of the learning); in the fundaments of Mathematical Education; and in the approaching of the autonarrative qualitative research. It involved six graduating students of the Basic Education of a state school of the 8th Regional Unit of Education of Castanhal – SEDUC/PA. In the method, it used itself an investigative questionary, WhatsApp, participant observation, an interdisciplinar Project, poll test and anamneses. The results pointed in the narratives Life Histories, and in these, the evidence of several inteligences, this way, all the participants manifested ability to creat, among them, three with ability to solve problem; ability to solve problem; for contributing in cultural context. Individually, it identified itself that, three manifested mathematical-logic inteligence, from them, it stood out itself one with one interpersonal, intelectual and leadership, and two with intrapersonal intelligence. One student manifested linguistic intelligence, musical and spatial; one presented interpersonal and pictorial intelligence; ando ne evidenced pictorial intelligence. From the construction experience of mathematical statements emerged the Inverse Mathematical Learning, which intelligences presented themselves in the inverse order of the convetional way from the way of learning: a) analise (perception, attention, memory), which it was stimulated from one object, one sentence, image, etc.; b) interpretation (sense, value, assignment), in which occured the validation about what has been analised; and, c) context (temporal, social, attitudinal), through the statement. The experience origined reflections about the necessity of changing in the teacher’s practice, from the indicators: teacher’s stare in the spectro of intelligences; curiousity, autoconfidence and reflection in and about the teacher’s practice; and, teacher’s purpose. If they are developed efetivelly these aspects will become enriching of the teacher’s practicing in and to the inclusion.